ANALISIS MAKNA KONTEKSTUAL DALAM PERCAKAPAN SEHARI-HARI MASYARAKAT MANDAR KECAMATAN PULAU LAUT TANJUNG SELAYAR KABUPATEN KOTABARU - Husni Mubarak; Andi Muhammad Yahya (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2022)
The aims of the research are to describe the use of contextual meanings found in the daily conversations of the Mandar community in Gosong Panjang Village, Pulau Laut Tanjung Selayar District, Kotabaru Regency. Describing the influence of regional languages on daily conversations in the Mandar community is not in accordance with the purpose of the conversation. This reasearch use a descriptive qualitative research method that clearly describes. The techniques of data collection in this research are observation, documentation and analysis with the listen method, note method and record method. The results showed that the contextual meanings in the daily conversations of the Mandar people used in these conversations were the words iyye, ita, and tau. The influence of the local language on the daily conversation of the Mandar people is not in accordance with the purpose of the conversation, because the existence of a conversation in an interaction between one another is sometimes not in accordance with the objectives of the interlocutor. Key words: Contextual Meaning, Conversation, and Mandar Society.